Optimal Auction with Resale - Zhoucheng Zheng, Charles (Econometrica, 2002)
This paper investigates the design of seller-optimal auctions when winning bidders can attempt to resell the good. In that case, the optimal allocation characterized by Myerson (1981) cannot be achieved without resale. I find a sufficient and necessary condition for sincere bidding given the possibility of resale. In two-bidder cases, I prove that the Myerson allocation can be achieved under standard conditions supplemented with two assumptions. With three or more bidders, achieving the Myerson allocation is more difficult. I prove that it can be implemented in special cases. In those cases, the Myerson allocation is generated through a sequence of resale auctions, each optimally chosen by a reseller. Copyright The Econometric Society 2002.